Human Rights Protection in Trade: A Challenge - Birkah Latif; SM. Noor; Juajir Sumardi; Irwansyah Rawydharma (PADJADJARAN Jurnal Ilmu Hukum (Journal of Law), 2018)
AbstractIn a global economy, trade is a key element of states’ economic development. People performs various forms of trade since the beginning of time to the modern day. The debate over the protection of human rights has been excluded in the interests of trade since the occurrence of trade liberalization, despite codification of regulations through international institutions. The purposes of this paper are to analyze whether there are mechanisms for the protection of human rights and trade and to be an effort linking the human rights protection and trade. It is concluded that the protection of human rights in trade has not yet become something elaborated specifically in economic policies. First, in international cooperation, organizations such as WTO and international CSOs can do the propaganda of human rights and trade. Secondly, the government takes public choices and needs to shape the practices of human rights and trade. The WTO looks hesitant in performing its role; it especially moves around trade only. However, the insistence of mutual needs is voiced through the Millennium Development Goals (MDGs) program, Sustainable Development Goals (SDGs), as well as various other protections such as ICESCR, IUU, etc. The establishment of UN Guiding Principles of Principles on Business and Human Rights (UNGPs) in 2011 becomes the latest momentum for the framework to improve standards and practices of business and human rights. AbstrakDalam ekonomi global perdagangan merupakan kunci utama dalam peningkatan ekonomi negara-negara. Berbagai bentuk perdagangan telah dilaksanakan sejak dahulu hingga sampai kepada bentuk modern saat ini. Perdebatan atas perlindungan hak asasi manusia yang tersingkirkan demi kepentingan perdagangan telah dimulai sejak terjadinya liberalisasi perdagangan sekalipun telah dilakukan kodifikasi peraturan melalui lembaga internasional. Kasus-kasus yang menimpa mengantarkan pada tujuan dari tulisan ini yang ingin menganalisa isu atas: apakah terdapat mekanisme perlindungan terhadap hak asasi manusia dan perdagangan? serta bagaimanakah upaya yang dilakukan untuk dapat menautkan antara perlindungan hak asasi manusia dan perdagangan. Dari penulisan ini disimpulkan bahwa perlindungan atas hak asasi manusia yang berkaitan dengan perdagangan belum menjadi sesuatu yang dibahas khusus di dalam kebijakan ekonomi. Pertama, dibutuhkan kerjasama internasional, organisasi seperti WTO dan CSO internasional dapat mempropagandakan agenda  perlindungan hak asasi manusia di dalam perdagangan. Peran dari WTO dirasakan “agak ragu” terlebih dengan melihat landasan bergeraknya yang fokus pada perdagangan semata. Namun, desakan atas nama kebutuhan bersama di suarakan melalui program Millennium Development Goals (MDGs)-Sustainable Development Goals (SDGs) dan juga berbagai proteksi lainnya seperti ICESCR, IUU dan lainnya. Setelah UN Guiding Principle on Business and Human Rights (UNGPs) lahir di tahun 2011 menjadi momentum terbaru dalam kaitannya kerangka kerja untuk meningkatkan standar dan praktik terkait bisnis dan hak asasi manusia.DOI: https://doi.org/10.22304/pjih.v5n2.a9